Short message service (SMS) reminders improve treatment attendance in alcohol dependence, but are less effective for patients high in impulsivity. (December 2018) - Gullo, Matthew J.; Irvine, Kate; Feeney, Gerald F.X.; Connor, Jason P.
Abstract: Background and aims: Poor attendance increases the likelihood of relapse in alcohol dependence treatment. Evidence for improved attendance rates following introduction of short message service (SMS) appointment reminders is available in other health care domains. Patients high in impulsivity, characterized by a lack of planning, may particularly benefit from reminders. The study investigated the impact of SMS reminders on outpatient treatment attendance for alcohol dependence, and whether effects were moderated by impulsivity. Design: Prospective natural history study, with historical case control. Alcohol-dependent outpatients attending treatment received SMS appointment reminders (n = 102). These were compared to a historical control group (n = 91) treated prior to the introduction of SMS (totalling 1149 scheduled sessions). Setting: A metropolitan university hospital alcohol and drug outpatient clinic. Participants: 193 alcohol-dependent patients participated in a 12-week cognitive-behavioral therapy (CBT) program with a treatment goal of abstinence. Measurements: Trait impulsivity, severity of dependence, psychological distress at baseline. Attendance at each scheduled session. Findings: SMS reminders significantly increased probability of session attendance (0.90 versus 0.84, p = .02). The effect was qualified by a significant SMS x Impulsivity interaction whereby reminders became less effective with increasing patient impulsivity (p = .003). Conclusions: SMS appointment reminders improve treatment attendance for alcohol-dependent outpatients. More impulsive patients benefited less from reminders, suggesting their non-attendance may be related more to motivational factors. Highlights: SMS reminders increased alcohol outpatient attendance (p = .02) SMS led to 7% increase in probability of session attendance Impulsive patients benefited less from SMS reminders